Experts em educação: circulação e sistematização de saberes geométricos para a formação de professores (Rio de Janeiro, final do século XIX) - Conceicao, Gabriel Luis Da [UNIFESP] (2019)
This research aims to analyze how the geometric knowledge was systematized for the formation of teachers at the end of nineteenth century, put into circulation in Rio de Janeiro by ProfessorsAmélia Fernandes da Costa, Luiz Augusto dos Reis and Manoel José Pereira Frazão, teachers designated by republican power to Europe for mission of pedagogical studies. The period under investigation was a time of intense changes in the educational scenario in Rio, a time of many national and international debates, and it was also the time of dissemination of proposals concerning the intuitive method. It is based theoretically and methodologically on the precepts of Cultural History (CHARTIER, 2002, 2010, 2011, DE CERTEAU, 2008), wishing to contribute to the history of school culture (JULIA, 2001, CHERVEL, 1990). Teachers' professional knowledge, specifically the concepts of expert, expertise,knowledge to teach and knowledgefor teaching (HOFSTETTER; SCHNEUWLY, 2017) are used as a theoretical category and are used in the analysis of official reports produced by teachers and presented to the official bodies of the State and the articles of Pedagogical Journal, printed for the teachers. The analysis of the sources made it possible to verify that the activities of the teachers, as well as their active participation in the political questions and of the primary education,the call of the State for the mission, and consequent answer with the responsibility of producing an official report, fit them into the category of expert in education, allowing them to qualify. The thesis is that if they are experts, they participate effectively in the production of knowledge in the pedagogical field and. They put into circulation a proposal of a new "geometry for teaching" proper of the intuitive times, revealing the necessity of other knowledge to the teacher in addition to those coming from the disciplinary field of Geometry.This "geometry" was straight bound to drawings and to manual works, these also with proper characteristics, so that docent not enough to be an excellent designer, artist, or geometer, was needed of the teacher who taught the geometric knowledge a new professional knowledge. Thus, this is a reform of the Commission of 1891, as well as a strategy of creating policies of representation of teachers, in a rhythm of constant internationalization and school modernization.